MAKNA SIMBOLIK UBARAMPE TRADISI SLUP-SLUPAN OMAH DI DUKUH WONOSIDO KECAMATAN PLUPUH KABUPATEN SRAGEN - Vida Putri Anggraini; Kundharu Saddhono; Dewi Pangestu Said (Universitas Sebelas Maret, 2025)
Every cmmunity in a particular region possesses cultural traditions that can serve as symbols of identity, including the traditional of Slup-slupan Omah. The tradition of Slup-slupan Omah is one manifestation of Javanese culture found in the Sragen regency. The tradition pf Slup-slupan Omah is still practiced to this day due to the symbolicmeaning embedded within it. This research aims to (1) identify ubarampe in the Slup-slupan Omah; (2) analyze the symbolic meaning of ubarampe Slup-slupan Omah. The research method employed in this study is qualitative descriptive using a smiotic approach based on the principles of Charles Sanders Peirce. The data sources obtained for this research are from observation, documentation, and interviews. The technique used to research subjects is purposive sampling. The data validity test in this study employs thetheoretical and data source triangulation techniques. Data collection involves the use of interviews, observations, and document analysis. The data analysis technique in this study employs an interactive approach consisting of four components: data reduction, data presentation, and drawing conclusions. Based on the results of this research, the following conclusions can be drawn: (1) there are 35 forms of ubarampe used in the Slup-slupan Omah tradition, and (2) there are 35 symbolic meanings associated with the ubarampe in the Slup-slupan Omah tradition.